THE ROLE OF THE GREEK CATHOLIC CHURCH IN THE DEVELOPMENT OF THE COOPERATIVE MOVEMENT IN EASTERN GALICIA (1920S–1930S): AN ANALYSIS OF MODERN UKRAINIAN HISTORIOGRAPHY - KLISH, Andrii; SHYNKARYK, Yuliana (HUMANITARIAN STUDIES: HISTORY AND PEDAGOGY, 2025)
The role of the Greek Catholic Church in the development of the cooperative movement in Eastern Galicia in the 1920s–1930s is examined through the lens of modern Ukrainian historiography. Key approaches of scholars to analyzing the socio-economic, cultural, and educational activities of the clergy within the cooperative movement are reviewed. The participation of the clergy in establishing cooperatives, providing organizational support, and promoting educational initiatives aimed at ensuring the economic self-sufficiency of the Ukrainian population is highlighted. The positions of prominent church leaders, particularly Metropolitan Andrey Sheptytsky, on the cooperative movement are detailed. The unique aspects of the church's collaboration with Ukrainian cooperative organizations under conditions of Polish national discrimination are revealed. The impact of cooperatives supported by the Greek Catholic Church on the socio-economic advancement of the region is demonstrated. The cultural and educational role of the clergy in disseminating the cooperative idea and engaging diverse segments of the population in this movement is explored. Emphasis is placed on the importance of further investigations into local dimensions of cooperative activities and comparative analyses of Galicia's experience with that of other European regions. Future research opportunities are outlined in the context of integrating the economic, social, and ideological dimensions of the cooperative movement into historiographical discourse.